Discursive Constructions of Islamic Religiosity and Indonesian Muslim Identity in the Globalization Era - Muhammad Amin Saputra (ALSYS, 2026)
Amid globalization and the rapid expansion of communication technologies, Indonesian Muslim identity is increasingly negotiated within digital environments that reshape religious discourse, authority, and practice. This study aims to examine the dynamic negotiation of Indonesian Muslim identity in the digital era by drawing on Manuel Castells’s concept of the network society, Heidi Campbell’s digital religion framework, and Zygmunt Bauman’s notion of liquid modern life. Using a qualitative analytical-explanatory library research design, the study analyzes primary sources, including books and journal articles on digital media and Indonesian Islam, as well as secondary data from online religious communities, through interpretive discourse analysis. The findings show that digital platforms broaden the public sphere and enable Muslim actors, such as preachers like Felix Siauw and movements such as One Day One Juz (ODOJ), to combine traditional Islamic values with popular culture, visual aesthetics, and algorithmic logic. This process fosters forms of “Popular Islamism,” produces fragmented yet adaptive religious identities, and generates new practices of piety that challenge fixed religious authorities while intensifying contestation and adaptation in the post-Reformasi context. Although social media accelerates the circulation of religious discourse, it also requires new criteria of trust and legitimacy. The study concludes that Indonesian Muslim identity in the digital era is hybrid, adaptive, and resilient, shaped by ongoing technological mediation. These findings contribute to interdisciplinary discussions on digital religious subjectivities and offer practical insight into the dual role of digital media in shaping contemporary faith and society.